2020
DOI: 10.1097/icl.0000000000000705
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ocular Demodex Infestation in Children: An Epidemiological Survey in South China

Abstract: Objectives: To investigate the prevalence of and risk factors for Demodex mite infestation of the eyelashes in Chinese children. Methods: A total of 1,575 children were surveyed from June 2017 to January 2019 and stratified into two age groups: 3 to 6 and 7 to 14 years. All subjects underwent routine eye examination and lash epilation for Demodex mite identification and counting using microscopy. Demographic data and lifestyle habits were also recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…In the present study, it can be clearly seen that the young group had a higher prevalence of corneal changes involving the stroma, such as infiltration or ulceration, while SPK was the main corneal change in elderly people. Our previous research and the findings in this study provide strong support to D. brevis or D. brevis % as a risk factor for corneal changes in young patients with ocular demodicosis (13)(14)(15). This study revealed that there are relatively fewer D. brevis mites and milder corneal changes in elderly patients, which further supports our notions that D. brevis plays a more important role in the pathogenesis of ocular demodicosis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, it can be clearly seen that the young group had a higher prevalence of corneal changes involving the stroma, such as infiltration or ulceration, while SPK was the main corneal change in elderly people. Our previous research and the findings in this study provide strong support to D. brevis or D. brevis % as a risk factor for corneal changes in young patients with ocular demodicosis (13)(14)(15). This study revealed that there are relatively fewer D. brevis mites and milder corneal changes in elderly patients, which further supports our notions that D. brevis plays a more important role in the pathogenesis of ocular demodicosis.…”
Section: Discussionsupporting
confidence: 89%
“…To the best of our knowledge, this was the first time that Demodex infestation was detected in children without systemically immunocompromised status. Recently, we conducted an epidemiological survey and revealed a low Demodex mite count in 12.0% of healthy Chinese children aged between 3 and 14 years (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South China in 2021, the incidence of eye infections due to Demodex spp. was significantly higher in autumn and winter than in other seasons amongst 1,575 school-children (43). Apparently, there is consensus in the literature that Demodex spp.…”
Section: Discussionmentioning
confidence: 83%
“…La blefaritis por Demodex folliculorum es una condición común que afecta casi al 100% de las personas mayores de 70 años 1 . Puede también afectar a niños aunque la incidencia es menor (alrededor del 15%) 2 . La presencia de Demodex folliculorum se ha asociado en los últimos años a un número importante de condiciones oculares como síndrome de ojo seco 3 , disfunción de glándulas de Meibomio 4 , rosácea cutánea 5 y ocular, chalazión recurrente 6 , meibomitis 7 , querato-conjuntivitis 8 y neovascularización de la córnea 9 .…”
Section: Introductionunclassified